Effect of Vegetable Oils as Adjuvants on Immune Response to Polyvalent Foot and Mouth Disease Inactivated Vaccine - Mohamed A. Gamil (Egyptian Society for Animal Management, 2021)
Foot and mouth disease (FMD) is one of the most important viral diseases in Egypt and the main way for its control is sufficient vaccination. A vaccine that could improve early and long-lasting immunity by selecting the best adjuvants is the main target for veterinarians. In this study, different formulae from polyvalent inactivated FMD vaccine were prepared using different vegetable oils (Peanut oil, Olive oil, and Sunflower oil) supplemented with Ginseng saponin and compared with locally used Montanide ISA206 as alternative adjuvants. Evaluation of such formulae was carried out through the international quality control protocol for vaccine evaluation, vaccination of calves groups to follow up their cell-mediated immunity using lymphocytic proliferation assay and level determination of interleukine-6, interleukin12 by the fourth week post-vaccination. Humeral immune response was evaluated by recording serum neutralizing antibodies' protective values by the 6th week. All the prepared vaccine formulae were found to be potent for vaccinated calves, except the Olive oil vaccine showed week performance. Our data suggest that Peanut oil and Sunflower oil supplemented with Ginseng saponin could be used as adjuvants in polyvalent FMD vaccine with comparable results to conventionally used mineral oil Montanide ISA206.